2011
DOI: 10.4244/eijv6i8a170
|View full text |Cite
|
Sign up to set email alerts
|

Late outcomes of drug eluting and bare metal stents in saphenous vein graft percutaneous coronary intervention

Abstract: Late outcomes of drug eluting and bare metal stents in saphenous vein graft percutaneous coronary intervention.Aims: PCI with drug eluting stents (DES) has been shown to reduce restenosis and major adverse cardiac event (MACE) rates compared to bare metal stents (BMS) in native coronary vessels, although outcomes in saphenous vein graft (SVG) lesions are less clear. We retrospectively studied 388 consecutive patients admitted to our centre for SVG PCI to assess mortality and MACE outcomes (defined as composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…It is possible that there is an element of selection bias, for example, in the largest registry study involving over 1,000 patients 32 which also showed a mortality benefit associated with DES use, BMS were used in greater frequency than DES in more acute settings such as STEMI and “emergency” cases. In contrast, studies such as that of Lee et al 14 illustrated that DES were used more commonly in emergent cases presenting with acute coronary syndrome while other studies used in this analysis have shown that BMS and DES where used in similar frequencies in the acute setting 10,12,15,17,18,30,31 …”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…It is possible that there is an element of selection bias, for example, in the largest registry study involving over 1,000 patients 32 which also showed a mortality benefit associated with DES use, BMS were used in greater frequency than DES in more acute settings such as STEMI and “emergency” cases. In contrast, studies such as that of Lee et al 14 illustrated that DES were used more commonly in emergent cases presenting with acute coronary syndrome while other studies used in this analysis have shown that BMS and DES where used in similar frequencies in the acute setting 10,12,15,17,18,30,31 …”
Section: Discussionmentioning
confidence: 72%
“…Separate meta‐analysis of the randomized controlled trials 6,7 did not reveal any mortality benefit/adverse effect associated with DES use (OR 6.7; 95% CI 0.62–74.14; P = 0.12), although a separate meta‐analysis of data from registry studies alone 9–16 , 18,22 , 24–28 , 30–32 showed a similar reduction in the risk of mortality to the pooled analysis associated with the use of DES (OR 0.60; 95% CI 0.50–0.73; P < 0.0001).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations